Primary treatment of the prostate improves local palliation in men who ultimately develop castrate‐resistant prostate cancer. (23rd July 2013) - Won, Andy C.M.; Gurney, Howard; Marx, Gavin; De Souza, Paul; Patel, Manish I.
<x xml:space="preserve">Abstract</x> Objectives To determine whether local treatment of primary prostate cancer gives palliative benefit to men who later develop castrate‐resistant prostate cancer (CRPC). Local treatments of primary prostate cancer are defined as radical retropubic prostatectomy (RRP) or external beam radiation therapy (EBRT). Patients and Methods Patient records were reviewed in five different hospitals in Sydney, Australia, and 263 men with CRPC were identified. Eligible patients comprised men who had progressive disease during androgen deprivation therapy with castrate levels of testosterone. Clinical and pathological data were reviewed and evaluated using the chi‐squared test and relative risk analysis to determine the relationship between previous local prostate treatment and complications secondary to local disease. The end‐point was complications and morbidity attributed to cancer progression locally (i.e. from the prostate). Results Primary treatment of the prostate by either RRP or EBRT significantly reduces the incidence of local complications compared to no primary treatment (32.6% vs 54.6%; P = 0.001). RRP showed a significantly lower level of local complications compared to EBRT (20.0% vs 46.7%; P = 0.007). The most common local complications were bladder outlet obstruction (35.0%) and ureteric obstruction (15.2%). Conclusions The present retrospective analysis supports the hypothesis that primary local prostatic treatment gives palliative benefit to men who later develop CRPC. RRP was associated with the lowest local complication rate experienced at the stage of metastatic disease.